Automated Detection and Classification of Ponticulus Posticus from Digital Lateral Cephalograms- An Artifical Intelligence Based Retrospective Study - Jeevitha, Jebarani; Kumar S, Lokesh (Journal of Neonatal Surgery, 2025)
Context: Ponticulus Posticus (PP) is a clinically significant anatomical variant of vertebrae that may compress the vertebral artery and contribute to cervicogenic headaches. Traditional radiographic assessment of PP is often subjective and inconsistent. This study explores the application of artificial intelligence (AI) for detection and classification of PP from digital lateral cephalograms. Aim: To evaluate the accuracy of AI in detecting and classifying Ponticulus Posticus from digital lateral cephalograms. Settings and Design: An artificial intelligence based retrospective study. Methods and materials: A total of 1052 digital lateral cephalograms were selected, analyzed, and grouped as complete PP, partial PP, or absence of PP. Machine learning models in Orange® software, including Logistic Regression, Neural Network, and Naïve Bayes, were used for detection and classification. Results: Logistic Regression achieved an accuracy of 98.5%, 98%, and 97.4% in the detection and classification of complete PP, partial PP, and absence of PP, respectively, outperforming Neural network and Naïve Bayes. Logistic Regression also demonstrated higher AUC, F1 score, precision, and recall. ROC curve analysis confirmed its superior classification ability across all PP categories. Conclusions: AI, particularly Logistic Regression algorithm, is a reliable and promising tool for detecting and classifying Ponticulus Posticus in digital lateral cephalograms. Further validation using larger and more diverse datasets is recommended to enhance diagnostic precision.